HYPOALBUMINAEMIA RELATION WITH MORTALITY IN PRETERM NEONATES WITH SEPSIS (The Research of Medical Science Review, 2025)
Objective: To determine the association between hypoalbuminaemia and clinical outcomes in preterm neonates admitted to the neonatal intensive care unit (NICU). Place and Duration of Study: Department of Pediatric Medicine, The Children’s Hospital, Multan, Pakistan; over a period of six months following approval of the synopsis by the College of Physicians and Surgeons Pakistan (CPSP). Study Design: Descriptive Case Study. Methodology: Non-probability consecutive sampling was incorporated to enroll 127 preterm neonates receiving care in the NICU. We randomly grouped newborns into hypo albuminaemic and normal albuminamic categories through measurements taken during their initial 72-hour period. We collected and analyzed data through SPSS version 26 from preterm neonates regarding gestational age, birth weight and white blood cell count, platelet count, C-reactive protein levels alongside mechanical ventilation and inotropic support and NICU stay duration and mortality. The study employed Chi-square and logistic regression tests for analysis and established a p value of less than 0.05 for statistical significance. Results: The analysis of neonates revealed that hypoalbuminaemia affected 49.6% of patients. The hypoalbuminaemia group experienced higher patient death rates compared to the other group (p=0.012). Neonates with elevated CRP along with abnormal white blood cell counts and thrombocytopenia needed more mechanical ventilation (p=0.003) and inotropic support (p=0.014) in addition to displaying hypoalbuminaemia (p<0.001 and p=0.018 and p=0.032 respectively). The hypoalbuminemic neonates remained in NICU care for 12.6 ± 4.1 days which was substantially longer than the 9.2 ± 3.5 day NICU stay of normoalbuminemic patients (p=0.001). The analysis using logistic regression showed hypoalbuminaemia to be an independent factor which predicts mortality (adjusted OR=2.45, 95% CI: 1.11–5.43). Conclusion: The mortality rate of preterm newborns suffering from hypoalbuminaemia increases drastically while their bodies exhibit increased inflammation and require more intensive care. A serum albumin measurement taken early after birth appears to serve as both an economical and effective tool for risk assessment especially when used in resource-constrained areas such as Pakistan.